Analysis of etiological characteristics, risk factors and inflammatory factors in patients with postoperative infection following modified radical mastectomy - QIAN Fang, SUN Yongqiang, ZHANG Sihan, SONG Tianli (Zhongguo aizheng zazhi)
Background and purpose: Modified radical mastectomy is an important approach for treating breast cancer, but the risk of postoperative incision infection rate is relatively high, which can seriously affect the treatment outcome and prognosis of these patients. This study aimed to investigate the etiological characteristics, related risk factors and changes of serum inflammatory factors such as procalcitonin (PCT), C reactive protein (CRP), tumor necrosis factor-α (TNF-α), and interleukin-6 (IL-6) in patients undergoing modified radical mastectomy. Methods: The clinical data of breast cancer patients admitted to the Third People's Hospital of Zhengzhou from February 2019 to February 2022 were analyzed retrospectively. The pathogenic bacteria distribution and related risk factors of postoperative incision infection and the changes of serum inflammatory factors such as PCT, CRP, TNF-α and IL-6 were explored. This study has been approved by the Medical Ethics Committee of the Third People's Hospital of Zhengzhou (No.: 2025-04-014-K01) and acquired the informed consent. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) checklist was followed for this case control study. Results: A total of 128 patients were enrolled in this study. All patients underwent modified radical mastectomy were divided into infected group (n=22) and non-infected group (n=106) according to whether incision infection occurred after surgery. The incision infection rate after modified radical mastectomy was 17.19% (22/128). Twenty-six strains of pathogenic bacteria were isolated and cultured from 22 patients with postoperative incision infection. Among these, 16 strains were Gram-positive, accounting for 61.54% (16/26), mainly staphylococcus aureus and enterococcus faecalis. There were 10 Gram-negative strains, accounting for 38.46% (10/26), mainly escherichia coli and pseudomonas aeruginosa. The influencing factors of incision infection after modified radical mastectomy included preoperative neoadjuvant chemotherapy, intraoperative blood loss ≥300 mL, postoperative drainage volume ≥800 mL, drainage time ≥7 d, albumin <35 g/L, and white blood cell count <4×109/L (P<0.05). Multivariate logistic regression analysis showed that preoperative neoadjuvant chemotherapy, blood loss ≥300 mL, postoperative drainage volume ≥800 mL, duration of drainage time ≥7 d, albumin <35 g/L and white blood cell count <4×109/L were the independent influencing factors of incision infection after modified radical mastectomy (P<0.05). The peripheral blood levels of PCT, CRP, TNF-α and IL-6 in both groups increased compared with those before surgery, and those in the infected group were higher than those in the non-infected group (P<0.05). Conclusion: staphylococcus aureus and escherichia coli were the main pathogens after modified radical breast mastectomy. Preoperative neoadjuvant chemotherapy, blood loss ≥300 mL, postoperative drainage volume ≥800 mL, drainage time ≥7 d, albumin <35 g/L and white blood cell count <4×109/L were the independent influencing factors. The levels of serum PCT, CRP, TNF-α and IL-6 could be used as effective indicators to predict postoperative incision infection.